A2–A1–D–A1–A2 type non-fullerene acceptors based on methoxy substituted benzotriazole with three different end-capped groups for P3HT-based organic solar cells. Issue 40 (3rd October 2018) - Zhang, Qianqian; Xiao, Bo; Du, Mengzhen; Li, Gongqiang; Tang, Ailing; Zhou, Erjun
Abstract : In the last three years, the A2 –A1 –D–A1 –A2 skeleton has become increasingly popular in the design of non-fullerene acceptors (NFAs), and it could match particularly well with the classic p-type polymer of poly(3-hexylthiophene) (P3HT ). Abstract : In the last three years, the A2 –A1 –D–A1 –A2 skeleton has become increasingly popular in the design of non-fullerene acceptors (NFAs), and it could match particularly well with the classic p-type polymer of poly(3-hexylthiophene) (P3HT ). In this manuscript, we successfully synthesized three NFAs with this skeleton, namedBTA100, BTA101 andBTA103, where BTA units were substituted by methoxy groups and used as the middle electron-accepting unit (A1 ). To fine-tune the energy levels of the final BTA-based NFAs, three different electron-deficient building blocks, thiazolidine-2, 4-dione (TD), rhodanine (R) and 2-(1, 1-dicyanomethylene)rhodanine (RCN), were used as the end groups (A2 ), respectively. The introduction of methoxy groups into BTA can upshift the lowest unoccupied molecular orbital (LUMO) energy level of NFAs and realize high open-circuit voltage ( V OC ) organic solar cells. In addition, the O atom shows a weak interaction with the S atom in the neighbouring thiophene ring, which might be able to facilitate intramolecular charge transfer. The organic solar cell (OSC) device based onP3HT :BTA103 shows a high PCE of 5.31% with a V OC of 0.94 V, a J SC of 8.56 mA cm −2 and a FF of 0.66. In addition, it is worth noting that the V OC ofP3HT :BTA100 reached 1.34 V, which is one of the highest values for P3HT based solar cells. These results indicate that RCN is also an effective end group to construct NFAs and methoxy substitution is a simple method to improve the V OC forP3HT -based OSC devices.